100 global bright spots of green growth: Co-occurrence of nighttime light gain and forest gain, 1990–2015. (July 2022) - Busch, Jonah; Amarjargal, Oyut
Highlights: We find 100 places where economic growth and forest gain co-occurred. Two-thirds had higher-than-regional-average growth in service sector employment. Sectoral shift toward services may be a promising pathway for green growth. Abstract: Economic growth commonly occurs at the expense of environmental quality, but there are exceptions. Here we use satellite data to identify places where exceptional economic growth and exceptional environmental improvement co-occurred between 1990 and 2015. We term as "bright spots of green growth" those spatial clusters with the most cells above the 95th percentile within their world region in both economic growth (as proxied by increase in nighttime lights) and one aspect of environmental improvement (forest area). Because the locations of bright spots are sensitive to methodological choices, we applied two different approaches to identifying bright spots. The two approaches differed in their choice of nighttime lights data (DSMP-OLS in Approach A vs. DSMP-VIIRS composite in Approach B); choice of forest area data (forest cover vs. forest land-use); time period (2000–2010 vs. 1990–2015); and clustering technique (visual inspection vs. HDBSCAN algorithm). We identified the top five bright spots in each of ten world regions using each of two approaches, for a total of 100 global bright spots of green growth. We then tested the extent to which the attributes of bright spots were consistent with four non-mutually exclusive theories of green growth. Of the bright spots we identified, around two-thirds (65% using Approach A; 71% using Approach B) had significantly higher-than-regional-average growth in the share of labor employed in services, consistent with sectoral shift and "tertiarization." Fewer than half (38%; 46%) had significantly higher growth in income, consistent with the "Environmental Kuznets Curve" theory. Some (54%; 29%) had significantly higher growth in timber plantation area, consistent with "eco-industry"-driven rural development. Few (0%; 10%) had significantly higher growth in protected area coverage, consistent with public policy-induced forest conservation. Our findings suggest sectoral shift toward services, rather than rising income per se, may be a promising pathway for other regions seeking to combine economic growth and environmental improvement.